2018
DOI: 10.1016/j.jcmg.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Association Between High-Sensitivity Cardiac Troponin Levels and Myocardial Ischemia During Mental Stress and Conventional Stress

Abstract: In patients with coronary artery disease, myocardial ischemia during either mental stress or conventional stress is associated with higher resting levels of hs-cTnI. This suggests that hs-cTnI elevation is an indicator of chronic ischemic burden experienced during everyday life. Whether elevated hs-cTnI levels are an indicator of adverse prognosis beyond inducible ischemia or whether it is amenable to intervention requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…Taken together, our study shows, for the first time that the health of the coronary microvascular endothelium, at least partly determines coronary vasodilation during psychological stress, and the latter is reflected in the peripheral microvascular vasomotor responses during MS. These findings illustrate potential mechanisms in the pathogenesis of MSIMI that occurs frequently in patients with CAD and is associated with poor outcomes . We have previously shown that lower digital microvascular reactivity is associated with MSIMI .…”
Section: Discussionsupporting
confidence: 59%
“…Taken together, our study shows, for the first time that the health of the coronary microvascular endothelium, at least partly determines coronary vasodilation during psychological stress, and the latter is reflected in the peripheral microvascular vasomotor responses during MS. These findings illustrate potential mechanisms in the pathogenesis of MSIMI that occurs frequently in patients with CAD and is associated with poor outcomes . We have previously shown that lower digital microvascular reactivity is associated with MSIMI .…”
Section: Discussionsupporting
confidence: 59%
“…High‐sensitivity troponin I (hsTnI) was measured using the Abbott ARCHITECT analyzer (Abbott Laboratories, North Chicago, IL), which has a limit of detection of 1.2 pg/mL and an interassay coefficient of variation of <10% at 4.7 pg/mL. The upper reference limit (99th centile) ranges between 24 and 30 pg/mL in healthy populations, with a sex‐specific upper reference range of 36 pg/mL for men and 15 pg/mL for women . Samples were centrifuged twice before analysis and according to manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, those individuals who exhibit MSIMI are more likely to be women, have greater microvascular disease, have poorer left ventricular dysfunction, and display endothelial dysfunction, whereas exercise/pharmacological stress-induced ischemia is generally associated with men and those with larger and more diffuse coronary artery plaque. [4][5][6] Though there are sex differences in the rates of presentations of both MSIMI and exercise/pharmacological stress-induced ischemia, both men and women do exhibit both of these forms of ischemia. However, we do not know if the mechanistic factors that underlie these stress-induced ischemia differ by sex; for example, does MSIMI in women differ from MSIMI in men?…”
mentioning
confidence: 99%